2014
DOI: 10.1007/s12070-014-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of cagA Positive Helicobacter pylori Infection and Laryngeal Squamous Cell Carcinoma: A PCR Approach

Abstract: Helicobacter pylori is a gram-negative bacillus causing benign and malignant gastric diseases such as gastroesophageal reflux (GER). In larynx, H. pylori causes chronic inflammation and mucosal destruction that may lead to malignant changes. Although, H. pylori poses several virulence factors, cagA is probably the main factor in this regard. To evaluate the role of cagA gene in laryngeal squamous cell carcinoma (LSCC), a case-control study was conducted on patients with laryngeal complaints during 2010-2012. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…There is a positive correlation of M2 and survival and proliferation of melanoma cell [72] Cervical cancer CSF1 inhibition delays cervical tumor growth by attenuating the turnover of TAM and enhancing infiltration by CD8 ? T cells [74,75] TAM tumor-associated macrophage, MIF macrophage migration inhibitory factor, MCP1 monocyte chemotactic protein 1, CSF1 colonystimulating factor 1 Clin Transl Oncol chronic inflammation often gathered many macrophages and other inflammatory cells; macrophages in the mechanism of pregastric lesion and gastric cancer stage are still controversial [29][30][31].…”
Section: Tams and Gastric Cancermentioning
confidence: 99%
“…There is a positive correlation of M2 and survival and proliferation of melanoma cell [72] Cervical cancer CSF1 inhibition delays cervical tumor growth by attenuating the turnover of TAM and enhancing infiltration by CD8 ? T cells [74,75] TAM tumor-associated macrophage, MIF macrophage migration inhibitory factor, MCP1 monocyte chemotactic protein 1, CSF1 colonystimulating factor 1 Clin Transl Oncol chronic inflammation often gathered many macrophages and other inflammatory cells; macrophages in the mechanism of pregastric lesion and gastric cancer stage are still controversial [29][30][31].…”
Section: Tams and Gastric Cancermentioning
confidence: 99%
“…Burduk et al [36] reported that 23.3 % were cagA gene-positive. Amizadeh et al [5] stated that cagA gene was only present in 13.8 % of the case group and 31.9 % of the control group. So, it could be supposed that the microorganism may be an independent risk factor for LSCC as the laryngeal mucosa provides a reservoir for the bacteria [4].…”
Section: Discussionmentioning
confidence: 99%
“…They explained their results as all the Polish population is nearly infected with H. pylori, whereas Grbesa et al [3] detected H. pylori ureA gene using PCR in only 26 % of LSCC patients. Amizadeh et al [5] reported that H. pylori was detected in 33 % of patients with LSCC and 45.8 % of the control group. The high prevalence of H. pylori in our study may be attributed to the agricultural environment of North Delta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have maintained H. pylori as a risk factor in laryngeal SCC, [21][22][23] but other studies disagree. [24][25][26] These discrepant results might depend on the various detection methods for H. pylori, the incidence of H. pylori infection in the general population, and subject inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%